Percepatan Produksi Karya Sastra Mahasiswa Program Permata Merdeka Dengan Memanfaatan Voice Typing - Misnawati Misnawati; Petrus Poerwadi; Patrisia Cuesdeyeni; Muhammad Saibani Wiyanto; Nirena Ade Christy; Syarah Veniaty; Ibnu Yustiya Ramadhan; Diplan Diplan; Anwarsani Anwarsani; Siti Rahmawati (FKIP Universitas Palangka Raya, 2022)
This study aims to: (1) describe how to use voice typing by Permata Merdeka students. (2) describe the PPKSM model by using the voice typing of Permata Merdeka students. (3) Describe the form of literary works produced by the students of the Permata Merdeka program by using voice typing.This research method uses a qualitative approach. Qualitative research is a way to interpret and present data in descriptive form. The existing data are then interpreted and analyzed. This research resulted in: (1) how to use voice typing for Permata Merdeka students. (2) PPKSM model by utilizing voice typing of Permata Merdeka Program students. (3) the form of literary works produced by students of the Permata Merdeka program by utilizing voice typing. This innovative applied research TKT is at level six, namely demonstration of a system/subsystem model or prototype in a relevant environment. This study demonstrates the PPKSM (Accelerated Production of Student Literary Works) model by using voice typing to Permata Merdeka students who programmed the Literary Creative Writing course.